p53, c-myc p62 and proliferating cell nuclear antigen (PCNA) expression in non-Hodgkin's lymphomas. - Korkolopoulou, P (1994)
AIMS--To investigate the immunohistochemical expression of p53 protein in non-Hodgkin's lymphomas (NHL) and its relation to that of c-myc p62 oncoprotein and proliferating cell nuclear antigen (PCNA). METHODS--Paraffin wax embedded tissue from 90 non-Hodgkin's lymphomas (72 B cell and 18 T cell) was stained immunohistochemically for p53 protein, c-myc p62 oncoprotein, and PCNA using the monoclonal antibodies DO7, c-myc 1-9 E10, and PC-10, respectively. RESULTS--Of the non-Hodgkin's lymphomas studied, 55 (61%) stained positively for p53 protein. The proportion of positive cases increased from low grade non-Hodgkin's lymphoma and was higher in tumours of T cell origin. The percentage of positive cells (labelling index or LI) was significantly lower in low grade non-Hodgkin's lymphoma, but no difference was established between intermediate and high grade non-Hodgkin's lymphoma. In a large proportion of low grade non-Hodgkin's lymphoma the LI was below 1%. c-myc p62 immunoreactivity was identified in all cases. A significant positive correlation was established between p53 LI and c-myc p62 LI (rs = 0.453) as well as between p53 LI and PCNA LI (rs = 0.338). CONCLUSIONS--p53 immunoreactivity was present in about half the cases of non-Hodgkin's lymphoma and was related to the grade of malignancy and possibly to the B or T cell origin of the tumour. It was also associated with the proliferation state as expressed by PCNA LI and c-myc p62 expression, indicating that the expression of these three cell cycle-related genes might be interrelated.